The Influence Of Promotion And Customer Behavior On The Decision To Pursue Postgraduate Studies Mediated By Trust - Cahaya, Yohanes Ferry; Siswanti, Indra; Syamsunasir, Syamsunasir (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2025)
This study examines the influence of promotion and customer behavior on the decision to continue studying for a Master's degree with trust as a mediating variable. Using a quantitative approach with PLS-SEM analysis, the study found that customer behavior has a significant direct influence on the decision to continue studying (β=0.661, p<0.001), while promotion and customer behavior have a significant effect on the formation of trust. However, trust was not proven to mediate the relationship between the independent variables and the decision to continue studying, creating a